2009
DOI: 10.1371/journal.pone.0008461
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Signature of Invasive Potential in Metastatic Melanoma Cells

Abstract: BackgroundWe are investigating the molecular basis of melanoma by defining genomic characteristics that correlate with tumour phenotype in a novel panel of metastatic melanoma cell lines. The aim of this study is to identify new prognostic markers and therapeutic targets that might aid clinical cancer diagnosis and management.Principal FindingsGlobal transcript profiling identified a signature featuring decreased expression of developmental and lineage specification genes including MITF, EDNRB, DCT, and TYR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
112
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 45 publications
(56 reference statements)
11
112
1
Order By: Relevance
“…No correlation was observed between BCSC-1 expression and known markers of the G 1 ⁄ S transition (Kaufmann et al, 2008;Rother and Jones, 2009). In agreement with the in vitro findings, we found a positive correlation between BCSC-1 expression and genes involved in an invasive signature ( Figure S4B), including proteins involved in cell adhesion and cytoskeleton rearrangement (Jeffs et al, 2009).…”
Section: Significancesupporting
confidence: 90%
“…No correlation was observed between BCSC-1 expression and known markers of the G 1 ⁄ S transition (Kaufmann et al, 2008;Rother and Jones, 2009). In agreement with the in vitro findings, we found a positive correlation between BCSC-1 expression and genes involved in an invasive signature ( Figure S4B), including proteins involved in cell adhesion and cytoskeleton rearrangement (Jeffs et al, 2009).…”
Section: Significancesupporting
confidence: 90%
“…Recently, it has been shown that melanoma tumors are heterogeneous and composed of two main sub-populations clearly identified by two distinct transcriptional signatures (Haqq et al 2005;Hoek et al 2006;Jeffs et al 2009) . Hoek et al (2008) defined these populations as proliferative versus invasive.…”
Section: Introductionmentioning
confidence: 99%
“…Another group investigated the relationship between the gene expression profiles and clinical outcomes of 58 primary melanomas; 254 genes were found whose expression might have a role in predicting the clinical outcome of melanoma patients [Winnepenninckx et al, 2006]. A study was recently conducted with the major aim of identifying new prognostic markers and therapeutic targets that might aid clinical cancer diagnosis and management [Jeffs et al, 2009]. Global transcript profiling identified a signature characterised by decreased expression of developmental and lineage specification genes, including MITF, EDNRB, DCT, and TYR, and increased expression of genes involved in interactions with the extracellular environment, such as PLAUR, VCAN, and HIF1a.…”
Section: Gene Expression Profiling Of Melanomamentioning
confidence: 99%
“…Migration assays showed that the gene signature was correlated with the invasive potential of the cell lines, and external validation using publicly available data indicated that tumours with the invasive gene signature were less melanocytic and might be more aggressive. It is significant that the invasion signature could be detected in both primary and metastatic tumours, suggesting that gene expression conferring increased invasive potential in melanoma may occur independently of tumour stage [Jeffs et al, 2009]. The impact of genomics on understanding human melanoma progression and metastasis was summarised by Ren et al [2008].…”
Section: Gene Expression Profiling Of Melanomamentioning
confidence: 99%